2019
DOI: 10.1002/aqc.3026
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of marine Natura 2000 sites to produce ecosystem‐wide effects in rocky reefs: A case study from Sardinia Island (Italy)

Abstract: A number of policy measures have been adopted to cope with ongoing ocean degradation. Marine protected areas (MPAs) are among them. MPAs and their coverage have increased worldwide, including in EU waters. Natura 2000 (Nat2000) sites are at the core of the EU biodiversity conservation strategy and have been established to protect habitats and species included in two EU directives. Besides their specific objectives, their potential to contribute to an ecosystem‐wide conservation and their complementarity with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Moreover, FPAs effectiveness is often blurred by factors such as: (i) the lack of a proper spatial and temporal replication in the sampling design 16,19,20 ; (ii) improper features of the reserve itself ( e . g ., extension, location and enforcement 2123,24 ; (iii) the reliability of data coming from fishermen, especially if these data are provided by SSF operators 25 . These biases can result in concluding that FPAs do not target the whole set of conservation objectives which ultimately foster stakeholders’ scepticism about their reliability and efficacy 19,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, FPAs effectiveness is often blurred by factors such as: (i) the lack of a proper spatial and temporal replication in the sampling design 16,19,20 ; (ii) improper features of the reserve itself ( e . g ., extension, location and enforcement 2123,24 ; (iii) the reliability of data coming from fishermen, especially if these data are provided by SSF operators 25 . These biases can result in concluding that FPAs do not target the whole set of conservation objectives which ultimately foster stakeholders’ scepticism about their reliability and efficacy 19,26 .…”
Section: Introductionmentioning
confidence: 99%
“…These multiple-use MPAs differ in their establishment dates, in the extension of zones with different degrees of protection (A, B and C zones), in reserve effectiveness and in their management of the sea urchin harvest ( Table 1 ). However, their no-take areas (A zones) have recently shown a higher biomass of commercial fish compared to other protected areas (Natura 2000 sites) or unprotected sites ( Guidetti et al, 2019 ). In particular, in the MPAs a higher biomass of the urchin predators, the fish Diplodus sargus and Diplodus vulgaris , was found compared to outside the MPAs, about 1,600 g/125 m 2 and 500 g/125 m 2 in mean, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In effective MPAs, the density of prey species, whether fish or invertebrates, can be drastically reduced by the increased abundance of predators ( e.g. , Willis & Anderson, 2003 ; Sala et al, 2013 ; Giakoumi et al, 2017 ; Guidetti et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even small, well‐enforced and fully protected areas can have a significant ecological effect (Giakoumi et al, 2017). Several studies have shown that the density of prey species inside MPAs can be drastically reduced with an increase in predators (Willis & Anderson, 2003; Micheli et al, 2004; Sala et al, 2013; Giakoumi et al, 2017; Guidetti et al, 2019), although the enforcement level is the essential requirement to establish lost predatory interactions (Shears & Babcock, 2003; Guidetti, 2006a; Guidetti & Sala, 2007).…”
Section: Introductionmentioning
confidence: 99%